1975
DOI: 10.1029/rg013i004p00502
|View full text |Cite
|
Sign up to set email alerts
|

The West Antarctic Ice Sheet: Instability, disintegration, and initiation of Ice Ages

Abstract: An ice age model is proposed in which glacial-interglacial global climatic cycles are controlled by interactions between the cryosphere, hydrosphere, and atmosphere in the Atlantic environment. In the model, climatic change results from instabilities which develop in the snowfields or ice sheets of North America, Europe, and Antarctica. Disintegration of the West Antarctic ice sheet (that portion of the Antarctic ice sheet lying in the western hemisphere) initiates a chain of events which culminates in a globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
104
1

Year Published

1979
1979
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(105 citation statements)
references
References 62 publications
0
104
1
Order By: Relevance
“…There is considerable disagreement concerning the current state of equilibrium of the West Antarctic ice sheet. Hughes ( 1975) suggested that the ice sheet may be collapsing, and measurements of surface strain-rate that were made near the ice-sheet summit have been interpreted as indicating thinning of perhaps a few centimetres per year (Whillans, 1973(Whillans, , 1977Hughes, 1973;Thomas, 1976) . There is poor agreement between the various estimates of thinning-rate because of lack of information on the behavior of deep ice, and errors are difficult to assess since the result is rather sensitive to errors in the strain-rate measured perpendicular to the flow direction.…”
Section: The Stability Of the West Antarctic Ice Sheetmentioning
confidence: 99%
“…There is considerable disagreement concerning the current state of equilibrium of the West Antarctic ice sheet. Hughes ( 1975) suggested that the ice sheet may be collapsing, and measurements of surface strain-rate that were made near the ice-sheet summit have been interpreted as indicating thinning of perhaps a few centimetres per year (Whillans, 1973(Whillans, , 1977Hughes, 1973;Thomas, 1976) . There is poor agreement between the various estimates of thinning-rate because of lack of information on the behavior of deep ice, and errors are difficult to assess since the result is rather sensitive to errors in the strain-rate measured perpendicular to the flow direction.…”
Section: The Stability Of the West Antarctic Ice Sheetmentioning
confidence: 99%
“…Hughes, 1975) . These ice streams are often highly crevassed and they move at speeds which are 2-3 orders of magnitude greater than the ice sheet in which they are embedded.…”
Section: Introductionmentioning
confidence: 99%
“…I). This was attributed by Hughes (1975) to partial uncoupling of the base of the ice stream from its bed in the presence of large amounts of basal melt water. The stress-continuity requirement at the grounding line (Equation (9.2')) can be rewritten as an expression for the surface curvature on the ice-stream side of the grounding line by substitution of Equation (18):…”
Section: Discussionmentioning
confidence: 99%
“…If the bedrock depth increases inland from the grounding line, a rise in sea-level, for example, may lift a part of the ice stream free of its bed and effectively float the marginal zone of the ice stream, causing the grounding line to retreat inland to a region of greater ice thicknesses. Because of the strong dependence of the creep rate at the grounding line on ice thickness (Weertman, 1957), ice discharge at the grounding line will increase, resulting in down-draw of the ice-sheet surface in the drainage basin of the ice stream, a decrease in basal shear stress, and thus an acceleration of the collapse of the marine ice sheet (Hughes, 1975(Hughes, , 1981. These are all positive feed-back mechanisms that will amplify the initial perturbation.…”
Section: Clima Tological Role Of Ice Sheetsmentioning
confidence: 99%
See 1 more Smart Citation